A Goal-directed Quality Improvement Initiative to Reduce Opioid Prescriptions After Orthopaedic Procedures. (September 2019) - Choo, Kevin J.; Grace, Trevor R.; Khanna, Krishn; Barry, Jeffrey; Hansen, Erik N.
Abstract : Introduction: Orthopaedic surgeons are increasingly aware of deleterious effects of the opioid epidemic and the association between overprescription and diversion toward nonmedical opioid use or substance abuse. Opiate prescriptions at the time of hospital discharge have been identified as target for intervention. This study describes the successful outcome of a goal-directed intervention aimed at decreasing opioid overprescription by providing routine feedback to providers regarding their prescribing patterns. Methods: The amount of opioid medications, quantified as oral morphine equivalents (OMEs), provided to opioid-naive adult patients on discharge after orthopaedic surgery was prospectively collected. As part of an institutional quality improvement initiative, medical providers received reports every 2 months detailing median discharge OMEs prescribed, trended over time. After 6 months, a retrospective comparison was done between preintervention and intervention patient cohorts. Results: There were 401 patients in the preintervention cohort and 429 patients in the intervention cohort. Both groups were similar in regard to age, sex, rates of depression, surgical time, length of stay, orthopaedic subspecialty, and inpatient opioid requirement before discharge. Patients in the intervention cohort were prescribed markedly fewer opioid medications by 25%, equivalent to 20 tablets of 5-mg oxycodone IR (450 versus 600 OMEs, P < 0.001). Despite these opioid medications, opioid refill rates during the first 90 days after discharge did not markedly change between groups. Discussion: It is critical to judiciously treat postoperative pain while avoiding opioid overprescription. This study demonstrated the outcome of a goal-directed initiative to decrease overprescription of opioid medications. The initiative reduced discharge opioid prescriptions yet did not increase the risk of requiring a prescription refill in the postoperative period. This indicates that such an approach can result in opioid reduction, while still providing appropriate care and pain control for patients.